2020
DOI: 10.1007/s00216-020-02758-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a multi-analyte GC-MS method for the determination of 84 substances from plastic food contact materials

Abstract: Chemical substances shall not migrate from food contact materials (FCM) at levels that are potentially harmful for the consumers. Each of the current analytical methods applied to verify the migration of substances from FCM covers only one or few substances. There is a very limited number of publications on the development of analytical methods allowing the simultaneous determination of several classes of FCM substances, and almost none of them reported methods entirely dedicated to the ones in the positive li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…The applied analytical method was considered fit-for-purpose for this study, taking into consideration its existing thresholds and limitations [18,20]. The selection of the extraction solvent was based on previous studies, where it was shown that DCM is good extracting solvent for a majority of the FCM substances, PS monomers and oligomers, and NIAS [1,15]. Moreover, although a polar column (Innowax) has been used, the peak quality for the fatty acids was low, with their identification being based on NIST library and injection of standards.…”
Section: Analytical Methods and Identified Compoundsmentioning
confidence: 99%
See 4 more Smart Citations
“…The applied analytical method was considered fit-for-purpose for this study, taking into consideration its existing thresholds and limitations [18,20]. The selection of the extraction solvent was based on previous studies, where it was shown that DCM is good extracting solvent for a majority of the FCM substances, PS monomers and oligomers, and NIAS [1,15]. Moreover, although a polar column (Innowax) has been used, the peak quality for the fatty acids was low, with their identification being based on NIST library and injection of standards.…”
Section: Analytical Methods and Identified Compoundsmentioning
confidence: 99%
“…For the extraction, a method previously reported by our group [15] was slightly modified. Briefly, a lyophilized sample of 0.5 g of the collected insects' larvae was placed in a glass tube and extracted twice, with 1.0 mL of dichloromethane (DCM).…”
Section: Solid-liquid Extractionmentioning
confidence: 99%
See 3 more Smart Citations